Foreign direct investment determinants among polish companies: Greenfield investments vs. acquisitions - Małgorzata Jaworek; Włodzimierz Marian Karaszewski; Małgorzata Szałucka (Trends Economics and Management, 2018)
Purpose of the article: The purpose of this article is to identify FDI determinants that drive investment among Polish companies depending on their establishment mode choice (greenfield investment vs acquisition). Methodology/methods: Article presents selected results of these authors' own research conducted as part of Research Project No. N N112 322338 entitled "Investment Activity of Polish Enterprises Abroad - Factors and Effects", financed by the Ministry of Science and Higher Education. 64 companies (out of 622), which implemented a total of 279 FDI, participated in this research. The majority of these investors (57%) decided to invest their capital abroad in the form of greenfield-investments, nearly 21% only made acquisitions, and 22% undertook both greenfield-investment and acquisitions. Scientific aim: Increase in knowledge. Findings: Market-seeking determinants were the most important factors in the Polish direct investors' decision making process on investing abroad, regardless of the establishment mode choice (greenfield investments vs. acquisitions). Within this group of determinants, Polish investors have most frequently indicated "new market" as the most important factor. Conclusions: The study points to the fact that market-seeking factors explain most of the FDI undertaken by Polish firms. Resource seeking and efficiency seeking factors, falling in the category of economic factors, turned out to be of less importance for investors from Poland. Nevertheless, there were more significant differences in responses from the two groups of Polish investors among resource seeking factors.
Keywords: F21 F23; 650; Foreign Direct Investment